Penerapan Media Pembelajaran Dalam Meningkatkan Hasil Belajar Pendidikan Agama Islam di Kelas V UPTD SD NEGERI 04 Sarilamak Kecamatan Harau - Rio Satria; Syawaluddin Syawaluddin; Deslita Deslita; Restu Mutiara Sari; Puspani Utami Putri; Efnida Efnida (Jurnal Pendidikan Tuntas, 2024)
This research is motivated by the low learning outcomes of Islamic Religious Education of students at VII UPTD SMPN 1 Kecamatan Harau. Video media is the most appropriate and accurate learning media in conveying messages and will really help students' understanding. The aim of this research is to: determine the increase in results students learn Islamic Religious Education (PAI) through video learning media at VII UPTD SMPN 1 Kecamatan Harau. The data collection techniques used are tests and observations. The results of the research show that video media in PAI subjects is able to increase students' learning motivation, especially class V students at VII UPTD SMPN 1 Kecamatan Harau. Quantitative evidence can be seen of an increase in the motivation variable test from the first and second meetings. The test results also experienced an increase from pre-action results of 45%, in cycle I (first) it increased to 60%, in cycle II (second) it also increased to 90%. Meanwhile, qualitative evidence can be explained from the number of students who said they were happy the use of video media increases motivation and student concentration on subjects, PAI.